The Pattern of Cardiac Abnormality with Subarachnoid Hemorrhage and its Outcome in Patients (Bangladesh Journal of Neuroscience, 2026)
Objective: To evaluate the pattern of cardiac abnormality with subarachnoid hemorrhage and its outcome in patients.Methodology: This cross sectional study was conducted in the Department of Neurology and Department of Neurosurgery, BSMMU, Dhaka from 01.12.2021 to 30.12.2022 after IRB approval. A total of 72 Patients were selected from indoor of the Department of Neurology, and Neurosurgery, BSMMU, Dhaka according to inclusion criteria. Those who have fallen under exclusion criteria were excluded from the study. After ethical clearance from Institutional Review Board (IRB), 72 patients were selected following the mentioned inclusion and exclusion criteria. SAH patients within ten days after SAH were taken as a sample. Informed written consent was taken from each patient or his/her attendant. Proper history was taken, physical and neurological examination was done. And ECG, Troponin I, and Echocardiography was done including a CT of the brain. For conformation and location of aneurysm or arteriovenous malformation patients underwent Digital Subtraction Angiography (DSA) & CT angiogram of brain.Results: During the study, 34.7% were in the 47-57 years age group. Followed by 26.7% in 58-68of years age group, 20% in the 36-46 years age group and majority was male. 76% had hypertension whereas 29.3% had diabetes. Followed by 21.3% had smoking status & only 1.3% had a past family history. High-grade SAH (WFNS 4) was observed in 4 (6.7%) patients, and 12 (16%) patients had modified Fisher grade 4 SAH. 6.7% had acute myocardial infarction whereas 38.7% had troponin I level and 17.3% had higher levels of CK-MB, may mean that they had a heart attack or have other heart problem. Patients between 58 to 68 years old had the highest percentage (26.67%) of cardiac abnormalities and this outcome was significant (P= 0.000). Maximum female patients (26.67%) and maximum male patients (6.67%) had IHD (P=0.000).Conclusion: From this study, it concludes that, Cardiac complications after SAH are associated with an increased risk of ECG & laboratory changes, where IHD & MI cases were common. Patients with electrocardiogram abnormalities and stress cardiomyopathy need appropriate follow-up for the identification of a cardiac disease or risk factors for cardiovascular disease.